2009
DOI: 10.1155/2009/659820
|View full text |Cite
|
Sign up to set email alerts
|

Esophageal Papillomatosis Complicated by Squamous Cell Carcinoma

Abstract: Esophageal papillomatosis is a very rare condition that is believed to have a benign clinical course. Recent reports underscore the potential development of a malignancy in association with squamous papillomatosis of the esophagus. A case of esophageal papillomatosis complicated by the development of esophageal invasive squamous cell carcinoma diagnosed after esophagectomy, despite multiple nondiagnostic endoscopic biopsies, is described. The patient also developed squamous cell carcinoma in the oral cavity an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
1
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(59 citation statements)
references
References 21 publications
2
50
1
6
Order By: Relevance
“…Oesophageal papillomatosis is a very rare entity, with only 10 cases (including ours) reported in the literature 1 2. Squamous oesophageal papillomas are rare but are more common than papillomatosis.…”
Section: Introductionmentioning
confidence: 69%
See 1 more Smart Citation
“…Oesophageal papillomatosis is a very rare entity, with only 10 cases (including ours) reported in the literature 1 2. Squamous oesophageal papillomas are rare but are more common than papillomatosis.…”
Section: Introductionmentioning
confidence: 69%
“…Initial reports revealed that squamous papillomas are benign with no malignant transformation; however, recent reports have shown development of malignancy in the setting of squamous papillomas 5 6. We are reporting a rare and interesting case of a 51-year-old man with chronic dysphagia who was diagnosed with oesophageal papillomatosis, only the 10th case reported in the literature 1 2. This patient underwent oesophagectomy, after failed medical therapy, 4 years after initial diagnosis, and the postoperative specimen again confirmed oesophageal papillomatosis.…”
Section: Introductionmentioning
confidence: 87%
“…Daha çok genitoüriner trakt, cilt, üst solunum yolunu ve daha az s›kl›kta özofagusu tutabilir. Özofa-gus skuamoz hücreli Ca'n›n HPV ile iliflkili olabilece¤i bildirilmifltir (29,30).…”
Section: Tartifimaunclassified
“…Here, we present a rare case of extensive ESPs involving the entire esophagus and prominent cardiac gland hyperplasia involving the lower esophagus, which were subsequently complicated by adenocarcinoma of the EGJ [9,10].…”
Section: Introductionmentioning
confidence: 99%